Capacity of anchor of Hydrabolt rock bolts according to bore hole diameter - Giraldo Paredez, Emiliano Mauro (2016)
Rock mass support with rockbolts, is the greater application method in the rock excavation industry, because is necessary to carry out studies concerning this method of support. Among other things, there are parameters that directly influence on the anchor capacity of rockbolts, including incontrolable variables by man such as rock type, and variables that the man can control, like the bore hole diameter, which despite its great influence, little has been studied in this respect. The present study was conducted to determine the anchor capacity of Hydrabolt rockbolts, depending on the bond length and the bore hole diameter where they are installed. For that purpose, were conditioned to the site and the structure necessary to perform tests, simulating holes with tubes of 33, 36, 38 and 40 mm diameter making bond lengths of 1, 2, 3 and 4 foots. 64 tests were performed in San Marcos university (Lima - Peru). The results of the study show that the optimal diameter of bore holes where the Hydrabolt bolts should be installed is 38 mm, for any bond length.